LEARNING EXPERIENCES OF SOCIAL WORK STUDY PROGRAMME STUDENTS: TUTOR’S AND PEER SUPPORT - Kondratavičienė, Renata; Ilgūnė-Martinėlienė, Rita; Bertašienė, Inga (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The learning experiences of social work students are influenced by their interactions with tutors and peers, as well as the support they receive from them. Tutors play a crucial role in helping students understand theoretical concepts and apply them to real-world situations. Peer support fosters a collaborative learning environment where students can share insights and learn from each other’s experiences. The article examines the learning experiences of social work students in a study programme that emphasises tutor and peer support. The research aims to explore the role of tutor and peer support in a blended learning environment. A survey was conducted among 97 students who studied social work at a higher education institution in Lithuania in 2023. The study analysed the interactivity indicators, tutor support, and peer support. The results indicate that students highly valued the support provided by both tutors and peers. This support helped them to develop their professional identity, enhance their academic skills, and cope with the challenges of studying social work. The article offers insights for improving the quality of teaching and learning in this field.